2002
DOI: 10.3758/bf03194754
|View full text |Cite
|
Sign up to set email alerts
|

Attend to it now or lose it forever: Selective attention, metacontrast masking, and object substitution

Abstract: Metacontrast masking occurs when the visibility of a brief target stimulus is decreased by the subsequent appearance of another nearby visual stimulus. Early explanations of the phenomenon involved low-level mechanisms, but subsequent studies have suggested a role for selective attention. The results of three experiments presented here extend previous findings to the metacontrast paradigm. It is shown that the strength of metacontrast masking increases with the number of distractor items in a display, decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 30 publications
2
54
1
1
Order By: Relevance
“…Determining their relationships can help us reach a richer and more integrated understanding of visual information processing. Previous studies showed significant interactions between different types of masking and attention (e.g., Di Lollo et al, 2000;Ramachandran & Cobb, 1995;Tata, 2002). However, in most of these studies, the findings suffered from methodological artifacts and/or could be interpreted by alternative accounts (rather than artefactual mask-attention interaction).…”
Section: Implications For Models Of Attentionmentioning
confidence: 70%
See 2 more Smart Citations
“…Determining their relationships can help us reach a richer and more integrated understanding of visual information processing. Previous studies showed significant interactions between different types of masking and attention (e.g., Di Lollo et al, 2000;Ramachandran & Cobb, 1995;Tata, 2002). However, in most of these studies, the findings suffered from methodological artifacts and/or could be interpreted by alternative accounts (rather than artefactual mask-attention interaction).…”
Section: Implications For Models Of Attentionmentioning
confidence: 70%
“…In particular, the object-substitution model of masking, which was derived from the common-onset masking experimental paradigm, posited interactions between masking and attention and provided empirical evidence in support of this prediction. Other studies provided empirical evidence for maskingattention interactions in metacontrast masking (Ramachandran & Cobb, 1995;Shelley-Tremblay & Mack, 1999;Tata, 2002), raising the possibility that these interactions could be an essential component of all masking types. However, recent studies, using the common-onset masking paradigm, showed that the interaction between masking and attention was an artifact of ceiling/floor effects and provided evidence against the p r e d i c t i o n o f t h e o b j e c t s u b s t i t u t i o n m o d e l (Argyropoulos et al, 2013;Filmer et al, 2014Filmer et al, , 2015Pilling et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In metacontrast masking and object substitution paradigms, the magnitude of the masking effect varies in strength with attention (Ramachandran & Cobb, 1995;Enns & Di Lollo, 1997;Tata, 2002). In orientation discrimination (Morgan, Ward, & Castet, 1998), character recognition (Giesbrecht & Di Lollo, 1998), and oddball form and motion judgments (Kawahara, Di Lollo, & Enns, 2001), the magnitude of the attentional effects have been found to depend on whether backwardly masked displays are used.…”
mentioning
confidence: 99%
“…That is, metacontrast masking is obtained even with a centrally presented and attended target; in fact, this is the arrangement in which metacontrast masking is traditionally used (Alpern, 1952(Alpern, , 1953Breitmeyer & Ögmen, 2006). However, the magnitude of metacontrast masking increases when spatial attention is dispersed during the presentation of the target (e.g., number of distractors in the target array) and attenuated when rapid attention to the target is facilitated in such arrays (Shelley-Tremblay & Mack, 1999;Tata, 2002). While the label metacontrast masking was not used, this interaction between attention and metacontrast masking was first noticed decades ago.…”
Section: Metacontrast Maskingmentioning
confidence: 99%